A Simpler Verifiable Gift Tax - Gerzog, Wendy C. (Columbia Journal of Tax Law, 2015)
The author proposes reforms to simplify the current federal gift tax system, foster uncomplicated outright transfers, eliminate valuation distortions, and increase taxpayer return compliance. In order to obtain those results, the author’s simpler verifiable gift tax would incorporate hard-to-complete rules of transfer taxation, harmonize the gift and estate tax regimes, and grant gift tax preference inducements to encourage the filing of timely gift tax returns.